Guillain-Barré syndrome as an early complication of a new coronavirus infection SARS-CoV-2 (clinical case) - K.Yu. Lytvyn; V.V. Mavrutenkov; О.M. Yakunina; Z.O. Chykarenko; O.O. Bilokon; M.O. Turchyn (Medičnì Perspektivi)
The new strain of coronavirus SARS CoV-2 can affect any organ and system of the body. The pathogenesis of these lesions is due to both direct damage to body cells by the virus and the development of immunopathological reactions that can lead to demyelinating diseases of the nervous system. The article presents a clinical case of the development of Guillain-Barré syndrome associated with coronavirus disease in a 71-year-old man who developed after infection with a new strain of SARS CoV-2 virus. The man was hospitalized on the seventh day of the disease with complaints of unproductive cough, weakness, fever in the range of 37.5-38.7°C, shortness of breath during exercise. The clinical diagnosis was confirmed by the presence of SARS CoV-2 RNA in the nasopharyngeal secretion. According to digital radiography, the presence of interstitial pneumonia was determined. Against the background of treatment, the condition gradually improved and on the 14th day after the onset of the disease, a negative PCR result (SARS CoV-2 (-) RNA) was obtained. However, on the 16th day of hospital stay (23-24th days of the disease) he was diagnosed with polyneuropathy (Guillain-Barré syndrome), severe tetraparesis. Despite the therapy, the condition gradually deteriorated due to the progression of polyneuropathy. On the 9th day after the onset of neurological symptoms (25th days of illness), on the background of severe neurological deficits, the signs of respiratory and cardiovascular insufficiency developed, which led to the death of the patient. It has been shown that the course of Guillain-Barré syndrome, which developed after infection with a new strain of SARS CoV-2 virus, in this case has a severe course and lethal outcome of the disease. It is necessary to look for clinical predictors that would predict the occurrence of neurological complications in patients with coronavirus disease.